PENERAPAN PENATAAN RUANG TRADISIONAL DI DESA ADAT KESIMAN, KOTA DENPASAR. - Gede Taji Iswara Sakti; Ni. G. A. Diah Ambarwati Kardinal; I Gusti Putu Anindya Putra (UNHI PRESS, 2022)
This study tries to identify the traditional spatial elements in the spatial structure and pattern in the Kesiman Traditional Village. Through qualitative methods and descriptive approaches, this study produces a spatial analysis that focuses on the application of Catuspatha and Sanga Mandala in the Kesiman Traditional Village. Catuspatha, which is the embodiment of cultural spatial symbols, in its application is transformed into a center for environmental activities with the roles and functions of each of its elements. Puri as the center of government, wantilan as a cultural center, peken as an economic center and open space as a social center. The four elements are divided by crossroads with the values contained in each quadrant. While Sanga Mandala consists of nine zones with a cosmologically hierarchical values from sacred, neutral and profane. This value order is formed from the vertical and horizontal ties of the three parts Utama, Madya, Nista, which form nine zones. Traditional spatial planning in every traditional village in Bali has its own characteristics and uniqueness, including the Kesiman Traditional Village which is rich in heritage from previous kings. The results of the study show that these traditional values are now experiencing changes in their spatial aspects along with the times from the ancient kingdom to the current era of modernization.